Pengaruh Guided Imagery Terhadap Skala Nyeri Pada Pasien Kanker Payudara Di Ruangan Rawat Inap Bedah Wanita RSUP Dr. M.Djamil Padang - Weny Amelia; Dewi Irawaty; Riri Maria (Jurnal Keperawatan Muhammadiyah, 2020)
ABSTRACTBreast cancer is the abnormal growth of cells that occurs in breast tissue. The problem often arises in patients with breast cancer is pain. Guided Imagery is a nonpharmacological strategi that can reduce pain. The aimed of this research was to identify the effect of Guided Imagery to the scale of pain in breast cancer patients admited in female surgical wards Dr. M. Djamil hospital Padang. The study design was quasi experimental using pretest-posttest with control group and using a consecutive sampling. The number of samples was 30 people (15 control group and 15 the intervention group). Pain was measured by the Numeric Rating Scale (NRS). The statistical test was two different test mean. The result was a significant effect on the pain scale Guided Imagery in breast cancer patients (P Value = 0.000; α = 0.05). There was a significant relationship between the age with the pain scale (P Value = 0.000; α = 0.05), and there is no relationship between the tribe with the pain scale. The results of this study recommends Guided Imagery being implemented as nursing interventions to reduce the pain of breast cancer.